2013
DOI: 10.1111/j.1365-2990.2012.01306.x
|View full text |Cite
|
Sign up to set email alerts
|

Review: Microglia of the aged brain: primed to be activated and resistant to regulation

Abstract: Innate immunity within the central nervous system (CNS) is primarily provided by resident microglia. Microglia are pivotal in immune surveillance and also facilitate the coordinated responses between the immune system and the brain. For example, microglia interpret and propagate inflammatory signals that are initiated in the periphery. This transient microglial activation helps mount the appropriate physiological and behavioral response following peripheral infection. With normal aging, however, microglia deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
488
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 643 publications
(546 citation statements)
references
References 157 publications
32
488
0
7
Order By: Relevance
“…Several conditions of priming exist. For instance, aged rodents demonstrate increased expression of mRNA and protein markers of inflammation following LPS challenge (Kumar et al, 2013;Norden and Godbout, 2013;Norden et al, 2015aNorden et al, , 2015b. In addition to aging, similar priming effects have been reported in microglia from patients with neuropsychiatric disorders including traumatic brain injury (Fenn et al, 2014) and neurodegeneration (Norden et al, 2015a).…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 75%
See 1 more Smart Citation
“…Several conditions of priming exist. For instance, aged rodents demonstrate increased expression of mRNA and protein markers of inflammation following LPS challenge (Kumar et al, 2013;Norden and Godbout, 2013;Norden et al, 2015aNorden et al, , 2015b. In addition to aging, similar priming effects have been reported in microglia from patients with neuropsychiatric disorders including traumatic brain injury (Fenn et al, 2014) and neurodegeneration (Norden et al, 2015a).…”
Section: Alternative Activation and Acquired Deactivation Statesmentioning
confidence: 75%
“…Astrocytes undergo phenotypic conversion during aging and can develop into the senescence-associated secretory phenotype (Salminen et al, 2011). This senescent phenotype exhibits exaggerated reactivity to immune activation and is associated with reduced glutamate clearance as well as the production of inflammatory cytokines (Haroon et al, 2015;Norden and Godbout, 2013).…”
Section: Immune Regulationmentioning
confidence: 99%
“…A recent study failed to demonstrate increased neuroinflammation with aging 10 despite the fact that microglial activation is an aging hallmark. 11 Another study demonstrated lack of microglial activity in patients with mild depression. 12 Although this particular depression phenotype might not have a neuroinflammatory component, TSPO binding was unexpectedly reduced in the depressed cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Rather Gal-3+ staining may simply indicate that the microglial cell is Bprimed^for phagocytic activation while the presence of LN3+ staining may indicate the cell is Bprimed^for inflammatory activation (Norden and Godbout 2013;Perry and Holmes 2014). Double labeling with LN3 and Gal-3 would indicate that both processes are available when necessary.…”
Section: Functional Classification Of Microglia By Immunohistochemistmentioning
confidence: 99%